(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article briefly presents the online teaching format, which has become widespread in recent years, its positive and negative aspects; it mainly suggests the most effective ways to apply it in the educational process. At the same time, a clear line is drawn between the concepts of teaching and education, recommendations are made to clarify the role and place of online and face-to-face formats in the modern education system at school and university.The active use of the online format in extreme conditions made it possible to evaluate its advantages. However, its excessive application in some areas, for example, in primary education, revealed its downsides, which were inevitable in case of further use of the format. An analysis of the literature (Barbour M.K., Borup J., Wieneker O.S., Johnson N., Lowes S., Solovyov A., Frey T., Sweller J.) shows that in their works, the researchers have considered and described in detail the advantages and disadvantages of the online format, highlighting the positive aspects of online learning, especially in extreme conditions. There are proposals for online learning in certain parts of the education chain, but there is no systematic approach to assessing its role in the educational process and identifying the need for its proportional application. The purpose of our work is to fill this gap in the education system at school and university, which determines the relevance of this study, its theoretical and practical significance. Research methods: study and analysis of literature on the research problem; study and analysis of best practices, normative, educational documents in this area; generalization of theoretical and empirical data. The scientific novelty of the study lies in the fact that it substantiates and defines the Internet foundations for building a modern education system, presents recommendations on the effective combination of online and traditional formats at different levels of education at school and university. Keywords: online format, education, training, modern education system